Sutta-Nipata - Pali Text Society; Dines Andersen; Helmer Smith (London : Pali Text Society, 1965)
Commentary on the Buddhist canonical work.
Master microform held by: DLC.
Microfiche.
Keywords: Tripitaka. -- Commentaries; Buddhist monasticism and religious orders -- Rules